Optimization of the Semarang Police Public Relations Cyber Troops Team in Preventing Hate Speech During the Covid-19 Pandemic - Wahyu Nugroho Saputro (Advances in Police Science Research Journal, 2022)
This research is motivated by the high number of cyber crime cases in Indonesia, especially hate speech. The impact of hate speech is very broad because hate speech usually attacks certain groups or ethnicities so that it has a broad impact on security and order in society. The Indonesian National Police through the Public Relations Division actually has a Bureau in charge of managing social media. However, its implementation is still considered less than optimal because of the high number of hate speech cases that occur in the community. This study aims to determine the implementation of hate speech prevention on social media, the supporting and inhibiting factors of the implementation and trying to optimize the implementation of hate speech prevention on social media. The analytical knife used includes Scientific Perspective Management theory, Decision Support System theory and crime prevention theory. The concepts used are the concept of hate speech, the concept of social media, and the concept of optimization. The approach used is a qualitative approach with analytical descriptive. Data collection methods include interviews, observation and document study. The results of the study found that the prevention of hate speech carried out by the Semarang Police Public Relations Cyber ​​Troops Team was lacking because the Cyber ​​Troops Team members did not understand the definition of hate speech, did not explore the elaboration of articles on hate speech and the circular letter of the Indonesian National Police that regulates it, therefore prevention is not optimal. . Coupled with the profiling ability carried out by members of the Cyber ​​Troops Team, they are still less proficient. In this study, the author tries to offer alternative solutions through the creation of a cyber patrol guide book which the author formulated with experts in the field. The book contains the differences between the Cyber ​​Public Relations Team and Cyber ​​Crime, the classification of harsh words, the differences between real, fake and take over accounts and how to do their profiling. It is hoped that this guidebook can be used properly by members of the Cyber ​​Troops Public Relations Team of the Semarang Police.